2020
DOI: 10.15581/003.33.2.49-63
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the factors that determine engagement in podcasting: design from the users and podcasters’experience

Abstract: The current media ecosystem offers enormous participatory possibilities to media audiences that, in this way, have the opportunity to engage in the co-creation of media discourse in ways unknown during the 20th century. Following the marketing 2.0 theories, the creation of attractive user experiences is considered as one of the aspects that the media increasingly take into consideration in order to get profitable content. The aim of this research is to detect the factors that influence engagement in podcasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Research has identified an individual's participation with a podcast at the point of consumption, either directly by interacting with the creators on social media or indirectly by researching references made during the podcast, as a key factor in a listener's user-centered engagement (García-Marín, 2020 ). It also highlighted how the environmental, situational, and social context in which a podcast listening experience takes place can be a limiting factor in the listener's ability to engage in these forms of participatory engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has identified an individual's participation with a podcast at the point of consumption, either directly by interacting with the creators on social media or indirectly by researching references made during the podcast, as a key factor in a listener's user-centered engagement (García-Marín, 2020 ). It also highlighted how the environmental, situational, and social context in which a podcast listening experience takes place can be a limiting factor in the listener's ability to engage in these forms of participatory engagement.…”
Section: Discussionmentioning
confidence: 99%
“…This data was collected as a quantitative measure of different aspects of participants' podcast listening engagement, adapted from the aspects of podcast listening engagement metrics originally presented by García-Marín ( 2020 ) and Tobin and Guadagno ( 2022 ) in order to reflect the present study's interest in environmental context. The data collected in this part of the study was analyzed to calculate the total number of responses provided by individual participants for each aspect of podcast listening engagement .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos datos derivan de variedad y extensión de dispositivos con conectividad a la red, de la aparición de los altavoces inteligentes y asistentes de voz, de las plataformas de streaming de audio (Martínez-Costa y Legorburu-Hortelano, 2021) o, entre otros, de la expansión del contenido sonoro en Internet a partir de 2020, coincidiendo con la pandemia de COVID19. Todo esto, como adelantaban Rime et al (2022), propicia una nueva experiencia de la escucha y la aparición de contenidos sonoros con experiencias más inmersivas, más directas y relacionales con el sonido (Piñeiro-Otero y Pedrero-Esteban, 2022) que se asocian a empoderamiento, participación o interacción, característicos del espacio digital y las redes sociales (García-Marín, 2020).…”
Section: Estado De La Cuestiónunclassified
“…This was in line with prior observations in the design of online courses, as well as the general communication in the digital environment. 9,10 However, it also became clear that an online attendance was subject to competing priorities, especially as it was practically difficult to get away from ongoing local work and often home activities. Keeping the audience's attention was paramount to a successful meeting.…”
Section: Experiences As Participants Of the University Health Network/international Society For Biological And Environmental Repositoriesmentioning
confidence: 99%